2014
DOI: 10.1167/iovs.13-13708
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-9 Mediates Photoreceptor Death After Blunt Ocular Trauma

Abstract: The time course of caspase-9 activation and the neuroprotective effects of inhibition suggest that caspase-9 initiates cell death in a proportion of photoreceptors after blunt ocular trauma and that an intravitreally delivered biologic inhibitor may be an effective translational treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…It is known that disks die from apoptosis, for which a causative explanation is still lacking (Fain et al ., ). One pathway triggering caspase‐mediated apoptosis is the formation of apoptosomes, involving caspase 9 activation by Cyt c and their binding to cytosolic Apaf‐1 (Blanch et al ., ). Our previous proteomic analysis showed that Cyt c was expressed in the disks and that ATP synthase in the disk was outward facing (Panfoli et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It is known that disks die from apoptosis, for which a causative explanation is still lacking (Fain et al ., ). One pathway triggering caspase‐mediated apoptosis is the formation of apoptosomes, involving caspase 9 activation by Cyt c and their binding to cytosolic Apaf‐1 (Blanch et al ., ). Our previous proteomic analysis showed that Cyt c was expressed in the disks and that ATP synthase in the disk was outward facing (Panfoli et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…9 Additionally, photoreceptor damage and degeneration after direct blunt ocular trauma has been well documented in human 34,35 and animal models. [36][37][38] Our method of whole globe histological analysis revealed an acute anterior uveitis, a finding not previously reported in studies utilizing the FPI model where instead delayed axonal swelling and damage to the optic nerve has been documented, as well as disruption of the bloodbrain barrier (BBB). 26 We did see BBB damage 24 h post LFPI, demonstrated by the immunohistochemical staining of mouse IgG at the injury site; additionally, a loss of BBB integrity using the bTBI model occurring within the 24 h post injury has been previously well established.…”
Section: Discussionmentioning
confidence: 76%
“…While we did not assess visual acuity in the bTBI mice, the loss of the photoreceptor layer observed would ultimately impair vision and this photoreceptor degeneration could mirror one of the mechanisms leading to vision loss seen in some human blast injuries 9. Additionally, photoreceptor damage and degeneration after direct blunt ocular trauma has been well documented in human34, 35 and animal models 36, 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of our blast model in the future may also include looking at the visual system injury effects over a wide range of reasonable pressures (e.g., 10 -30 psi), repetitive blasts or combined primary and secondary insults (e.g., blast followed by weight drop induced skull-concussion). Others have shown that repetitive low level blasts, head concussions, or blunt force trauma to the eyes alone can lead to severe retinal degeneration in mice and rats (Blanch, 2012(Blanch, , 2014Tzekov, 2014;Choi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of our blast model in the future may also include looking at the visual system injury effects over a wide range of reasonable pressures (e.g., 10 -30 psi), repetitive blasts or combined primary and secondary insults (e.g., blast followed by weight drop induced skull-concussion). Others have shown that repetitive low level blasts, head concussions, or blunt force trauma to the eyes alone can lead to severe retinal degeneration in mice and rats (Blanch, 2012(Blanch, , 2014Tzekov, 2014;Choi, 2015).Also, while behavioral impairments in visual acuity tracking reflex (i.e., optokinetics) have been looked at (Hines-Beard, 2012;Bricker-Anthony, 2014b), no one has attempted to translate the retinal injuries into actual loss of performance on vision dependent psychomotor tasks. Indeed, for blasted rats, we saw a 30% decrease in retinal signaling with a 2 and 3-fold more neuronal cell damage in their retinas and brain optic tracts, respectively; however, most rats still performed quite well on the visual discrimination task.…”
mentioning
confidence: 99%